The Implementation of Pull Out Learning to Grow Interest in Learning to Read In Dyslexic Children in Class IV Students of SDN 1 Wanasaba - Yuni Agustin; Aswasulasikin Aswasulasikin; Abdul Aziz; Zohrani Zohrani (IJE : Interdisciplinary Journal of Education, 2023)
Research aims to see how the pull out strategy influences to students' interest in learning to read dyslexia class IV SD Negeri 1 Wanasaba Year Teachings 2023. The type of research used is Quantitative research with Single Subject Research (SSR) design . In this research, researchers used samples 1 student namely students dyslexia . The data collection technique used by researchers is an observation instrument to see students in the learning process, tests to determine students' initial abilities, student questionnaire to determine students' interest in learning, And documentation in the form of photos. As well as technique analysis data Which used in this research namely testing the hypothesis using the t test with level significant 0.05. Results data observation show (30%) categorized as low. So can concluded bah student dyslexia on learning process before implementing the Pull Out interest learning model learn to read it Still low. Results study Also show bah strategy pull out learning included in the very well implemented category dyslexic students which can be seen from the results respondents (96%) who has an influence on dyslexic students' interest in learning and helps Teacher Also in give strategy Study for student Which own or need strategy special in the class. As for data mark pretest of 25 and the posttest value data is 85 . So, we can see the results from the t-count hypothesis test ≥ t-table (5.34522 ≥ 4.30265) then Ho is rejected and Ha accepted.